2019
DOI: 10.1186/s12939-019-1074-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining ‘actionable’ high- costhealth care use: results using the Canadian Institute for Health Information population grouping methodology

Abstract: BackgroundA small proportion of the population consumes the majority of health care resources. High-cost health care users are a heterogeneous group. We aim to segment a provincial population into relevant homogenous sub-groups to provide actionable information on risk factors associated with high-cost health care use within sub-populations.MethodsThe Canadian Institute for Health Information (CIHI) Population Grouping methodology was used to define mutually exclusive and clinically relevant health profile sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…The studies of high-cost users in Canada 10 and of medically complex patients in northern California 11 both defined their populations for a single time period (i.e., episodic health care use) rather than for those who were continually high-cost users in multiple subsequent years, and who arguably had the greatest potential for targeted interventions and cost savings. 12 Much of the previous work in this area lacks granularity and neglects the high turnover in the high-cost population over time.…”
Section: Identifying Subgroups Of Adult High-cost Health Care Users: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of high-cost users in Canada 10 and of medically complex patients in northern California 11 both defined their populations for a single time period (i.e., episodic health care use) rather than for those who were continually high-cost users in multiple subsequent years, and who arguably had the greatest potential for targeted interventions and cost savings. 12 Much of the previous work in this area lacks granularity and neglects the high turnover in the high-cost population over time.…”
Section: Identifying Subgroups Of Adult High-cost Health Care Users: ...mentioning
confidence: 99%
“…[5][6][7][8][9] A recent Canadian study of high-cost patients described the clinical and demographic profiles of the top 10% of individuals by cumulative cost accrued during a 2-year window. 10 They identified 7 high-cost subgroups: "long-term care," "palliative care," "major acute illness," "major chronic diseases," "major cancer," "major newborn" and "mental health. "…”
mentioning
confidence: 99%
“…Hasta la fecha, según el conocimiento de los autores, no se han publicado modelos predictivos latinoamericanos que hayan incluido información relacionada con los diagnósticos previos, datos suministrados de forma directa por el paciente, mediciones objetivas del estado funcional y la presencia de fragilidad, para identificar individuos con necesidades en salud. La importancia de estas investigaciones radica en la posibilidad de identificar subgrupos de adultos mayores con un riesgo más elevado de desenlaces adversos (10,(20)(21)(22). Estas herramientas podrían contribuir en la implementación de intervenciones específicas estratificadas según el riesgo basal al interior de los programas de atención de los adultos mayores con ECNT.…”
Section: Palabras Claveunclassified
“…Health systems worldwide are facing the challenge of increased health care costs and sustainability [ 1 , 2 ]. Previous studies [ 3 , 4 ] have shown that a small proportion of individuals spend the majority of health care resources.…”
Section: Introductionmentioning
confidence: 99%
“…This population is referred to as high-cost health care users (also high-cost beneficiary, high user, high spender, super-utilizer) [ 5 ]. Studies have found that high-cost health care users are a heterogeneous population, and heterogeneity may contribute to the fact that few interventions have demonstrated evidence of reliable success [ 2 , 6 ]. Most of these high-cost health care users are older adults [ 5 ].…”
Section: Introductionmentioning
confidence: 99%